TITLE-THE DIRECT AND INDIRECT EFFECTS OF DIFFERENT COMPONENT TRAITS ON YIELD IN SHORT GRAIN AROMATIC RICE (Oryza sativa Oryza sativa L.) OF ODISHA - DIBYA RANJAN DALEI (The Bioscan, 2019)
The present study was undertaken with the objective to determine the direct and indirect effects of different component traits on grain yield using path coefficient analysis to sort out the most promising genotypes for their future use in thirty indigenous aromatic rice cultivars. The experiment was carried out with 26 land races and 4 aromatic checks which were evaluated in randomized block design with two replications. The 1000-grain weight exhibited maximum positive direct effect on grain yield both at genotypic and phenotypic level. Out of different characters under study, panicle numbers/plant, total grains/panicle, days to 50% flowering and days to maturity exerted greatest indirect effect on yield via other traits. Single plant yield, days to maturity, 1000-grain weight had maximum contribution to genetic divergence.